PENGARUH STRUKTUR KEPEMILIKAN, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP NILAI PERUSAHAAN - Sholichah, Wulan Aminatus; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to examine the ownership structural, firm size, and leverage to the firm value. The independent variables in this research are management ownership, domestic institution ownership, foreign institution ownership, firm size and leverage. The samples are 10 manufacturing companies in the sector of consumer goods industries which are listed in Indonesia Stock Exchange and these companies have published their annual report in 2011-2013 periods. The collection of samples has been carried by using purposive sampling method. The data has been obtained from the annual report of the manufacturing companies in consumer goods industries which are listed in Indonesia Stock Exchange. The hypothesis is examined by using the multiple linear regressions analysis. The result of the research of determination coefficient value is 43% and each of management ownership, domestic institution ownership, foreign institution ownership, public ownership, firm size and leverage variables have significant influence to the firm value. Meanwhile, 57% of the disclosure of the firm value can be explained by other variables outside of the research model. The result of the examination of the hypothesis shows that foreign institution ownership, public ownership, firm size and leverage variables have positive influence to the firm value.Keywords: Ownership Structure, Firm Size, Leverage and Firm value.